The structural determinants of the US competitiveness in the last decades: a "trade-revealing" analysis - Massimo Del Gatto; Filippo di Mauro; Joseph Gruber; Benjamin Mandel (European Central Bank (ECB), 2012)
We analyze the decline in the U.S. share of world merchandise exports against the backdrop of a model-based measure of competitiveness. We preliminarily use constant market share analysis and gravity estimations to show that the majority of the decline in export shares can be associated with a declining share of world income, suggesting that the dismal performance of the U.S. market share is not a sufficient statistic for competitiveness. We then derive a computable measure of country-sector specific real marginal costs (i.e. competitiveness) which, insofar it is inferred from actual trade ows, is referred to as 'revealed'. Brought to the data, this measure reveals that most U.S. manufacturing industries are losing momentum relative to their main competitors, as we find U.S. revealed marginal costs to grow by more than 38% on average. At the sectoral level, the "Machinery" industry is the most critical.
Keywords: F12; F17; F19; 330; competitiveness; export shares; Firm heterogeneity; firm selection; Gravity Equation; marginal costs; productivity; Trade Costs